Simple taxonomy of the genetic global optimization - Schaefer, Robert (Computer Assisted Methods in Engineering and Science, 2002)
The paper tries to show the role that can be played by genetic optimization strategies in solving huge global optimization problems in computational mechanics and other branches of high technology. Genetic algorithms are especially recommended as the first phase in two-phase stochastic optimization. The self-adaptability of genetic search is shown on the basis of the mathematical model introduced by M. Vose. Main goals of adaptation are used as leading criteria in the simple taxonomy of genetic strategies.